Evaluating an enhanced quality improvement intervention in maternity units: PReCePT trial protocol. Issue 2 (24th May 2021) - Edwards, Hannah; Redaniel, Maria Theresa; Opmeer, Brent; Peters, Tim; Margelyte, Ruta; Sillero Rejon, Carlos; Hollingworth, William; Craggs, Pippa; Hill, Elizabeth; Redwood, Sabi; Donovan, Jenny; Luyt, Karen
Abstract : The UK's National Institute for Health and Care Excellence Preterm labour and birth guideline recommends use of magnesium sulfate (MgSO4 ) in deliveries below 30 weeks' gestation to prevent cerebral palsy and other neurological problems associated with preterm delivery. Despite national guidance, the uptake of MgSO4 administration in eligible women has been slow. National Health Service England has rolled out the PReCePT (PRevention of Cerebral Palsy in Pre-Term labour) quality improvement (QI) toolkit to increase uptake of MgSO4 in preterm deliveries. The toolkit is designed to increase maternity staff knowledge about MgSO4 and provides training and practical tools to help staff consider use in eligible women. The PReCePT trial compares the effectiveness of two different methods of implementing the QI toolkit (standard versus enhanced support). The standard support arm (control) receives the QI toolkit and regional-level support for a midwife/obstetric 'champion'. The enhanced support arm (intervention) receives this plus additional clinical backfill funding and unit-level QI microcoaching. It is funded by The Health Foundation. This is a cluster randomised controlled trial designed to include 48 maternity units randomised (2:1 ratio) to standard or enhanced support. Units are eligible for inclusion if they have 10 or more preterm (<30 weeks' gestation) deliveries annually and MgSO4 uptake of 70% or less. Randomisation is stratified by previous level of MgSO4 uptake. The QI intervention is implemented over 9 months. All units are followed up for a further 9 months. Blinding is not possible due to the nature of the intervention. The primary outcome is the proportion of MgSO4 uptake among eligible women at follow-up, adjusting for uptake before implementation of the toolkit. The effectiveness of the intervention will be assessed using weighted linear regression on data from the National Neonatal Research Database. Semistructured qualitative staff interviews will inform understanding of the process and outcomes. Economic evaluation will describe total costs and cost-effectiveness. Trial registration number SRCTN 40938673.